“Better is the Little That the Righteous Has than the Abundance of Many Wicked” (Ps 37:16): Social and Moral Stratification in Late Persian-Period Judah as Reflected by Psalm 37 - Botha, Phil J. (Journal for Semitics, 2020)
This paper offers a social-scientific analysis of Psalm 37, aiming to define its ideological purpose and textual strategy. The psalm is also read as part of the sequence of Pss 35–37 as it was arranged by the editors of Book I of the Psalms. Financial deprivation and public humiliation of a moral upright minority by an immoral upper class seem to have caused growing discontent and feelings of aggression among the psalmist’s in-group. The author of Psalm 37 assumes the role of a wisdom teacher in order to reprimand, exhort and encourage members of the in-group to stay true to their faith under trying circumstances.
free
Keywords: Psalm 37; righteous; social-scientific analysis; wicked; wisdom psalm